A polygeneration system for the methanol production and the power generation with the solar–biomass thermal gasification. (15th September 2015) - Bai, Zhang; Liu, Qibin; Lei, Jing; Li, Hongqiang; Jin, Hongguang
Highlights: A new polygeneration system is proposed to generate methanol and power. Endothermic reactions of the biomass gasification are driven by solar energy. The thermodynamic properties of the system are numerically investigated. The sensitivity of the economic performance of the system is evaluated. The superiorities of the proposed system is demonstrated. Abstract: A polygeneration system of generating methanol and power with the solar thermal gasification of the biomass is proposed in this work. The endothermic reactions of the biomass gasification are driven by the concentrated solar thermal energy in a range of 1000–1500 K. The syngas from the biomass gasification is used to produce the methanol via a synthesis reactor. The un-reacted gas is used for the power generation via a combined cycle power unit. The thermodynamic and economic performances of the polygeneration system are investigated. A portion of the concentrated solar thermal energy can be chemically stored into the syngas, and thus the energy level of the solar thermal energy is improved. Numerical simulations are implemented to evaluate the thermal performances of the proposed polygeneration system. The results indicate that H2 /CO molar ratio of the syngas reaches 1.43–1.89, which satisfies the requirements of the methanol synthesis. The highest energy efficiency and the exergy efficiency of the polygeneration system approximately are 56.09% and 54.86%, respectively. The proposed polygeneration system can achieve the stable utilization of the solar energy and the mitigation of CO2 emission, and thus a promising approach is introduced for the efficient utilization of the abundant solar and biomass resources in the Western China.